Analisis Efisiensi dan Produktivitas Bank Pembiayaan Rakyat Syariah di Jabodetabek Periode 2019-2023 - Zulva, Muhammad Zulva Zeta Zaidan; Sebastian Herman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the efficiency and productivity of BPRS in Jabodetabek, totaling 17 BPRS during the 2019-2023 observation period. This research uses the BCC or VRS model as a basic model in analyzing bank efficiency and productivity using Data Envelopment Analysis and the Malmquist Productivity Index. This research uses input variables, namely third party funds and operational expenses, as well as output variables, namely operational income and financing. The results obtained from efficiency analysis using DEA show that there are still many BPRS in Jabodetabek that have not achieved maximum efficiency. The average Jabodetabek BPRS efficiency score fluctuates from year to year during the period 2019 to 2023, with an overall average efficiency of 0.716648. Meanwhile, the average productivity of BPRS in Jabodetabek is 1,102. In 2020 there was a decline in the efficiency and productivity of BPRS due to the Covid-19 pandemic. But Back shows recovery in 2021 to 2023.